Barriers to Learning and Participation in School of Students with Dyslexia: Family Voices - Dolors Forteza; Laura Fuster; Francisca Moreno-Tallón (Universidad Autónoma de Madrid, 2019)
Achieving quality education refers us to education that must be inclusive and equitable, emphasizing the value of differences in order to improve teaching and learning experiences. But, there are still many who suffer processes of exclusion in school; those who have dyslexia make up a group damaged by poorly welcoming practices and center cultures. The present study is oriented to analyze the barriers that hinder their learning and the sequels that produce. From a biographical-narrative methodological approach, the voices of families, through the interview, reveal that there are multiple obstacles that, beyond problematizing the progress of their sons and daughters, harm their self-concept and self-esteem. The results show as main barriers those related to the lack of efficient school-family communication, classroom methodologies that by their nature magnify the difficulties in reading and writing impacting on learning, and the emotional impact produced by the absence of responses to the needs of students with dyslexia. Making these barriers visible is a commitment to the right to quality education for and with all in compulsory education.